Contributing Factors to Intradialytic Complications in Hemodialysis Patients - Arsa, Sandi Alfa Wiga; Rahmawati, Anita (Babali Publisher, 2023)
Introductioin : Intradialytic complications are still being debated among health workers in the Hemodialysis Unit in Hospitals, many factors can cause patients to experience complications during dialysis. This study aims to identify the factors that contribute to the incidence of intradialytic complications in order to minimize the incidence of complications. Methode : This study used a research design in the form of analytic descriptive with cross-sectional. The sampling technique was a consecutive sampling of 120 patients. The chi-square statistical test aims to examine differences in proportions. If the results of the bivariate test have p < 0.25, then these variables can be included in the multivariate model using multiple logistic regression analysis. Result : Candidate selection results, Hb (0,014), Fluid Compliance (0,221), Venous Access (0,236), IDWG (0,023), and Comorbid (0,006) have a p value less than 0.25. In the multivariate test obtained Comorbid (0,007; OR:2.361 ), IDWG (0,049;OR:-1,894), and Hb (0,047;OR: 0,922), it can be concluded that these three factors have a significant influence on the occurrence of intradialytic complications.The proportion of intradialytic problems that can be described by 5 variables, namely venous access, comorbidities, IDWG, HB, and adherence, is 24%, with the remaining 18% explained by other factors. Conclusion : Comorbid, interdialytic weight gain, and hemoglobin goal accomplishment all have a significant role in the occurrence of intradialytic complication. The findings of this study can be utilized to raise awareness of intradialytic consequences. This vulnerable population need effective management to manage the problems they are experiencing.